Mouse promyelocytic leukemia zinc finger protein (PLZF) regulates hepatic lipid and glucose homeostasis dependent on SIRT1 - Hu, Huiling; Sun, Nannan; Du, Haiyan; He, Yuqing; Pan, Kunyi; Liu, Xiuli; Lu, Xiaoxia; Wei, Jie; Liao, Mianmian; Duan, Chaohui (Frontiers in Pharmacology, 2022)
Previous studies have demonstrated that promyelocytic leukemia zinc finger protein (PLZF) promotes the expression of gluconeogenic genes and hepatic glucose output, which leads to hyperglycemia. However, the role played by PLZF in regulating lipid metabolism is not known. In this study, we aimed to examine the function of PLZF in regulating hepatic lipid and glucose homeostasis and the underlying mechanisms. The expression of PLZF was determined in different mouse models with regard to non-alcoholic fatty liver disease (NAFLD). In the next step, adenoviruses that express PLZF (Ad-PLZF) or PLZF-specific shRNA (Ad-shPLZF) were utilized to alter PLZF expression in mouse livers and in primary hepatocytes. For the phenotype of the fatty liver, histologic and biochemical analyses of hepatic triglyceride (TG), serum TG and cholesterol levels were carried out. The underlying molecular mechanism for the regulation of lipid metabolism by PLZF was further explored using luciferase reporter gene assay and ChIP analysis. The results demonstrated that PLZF expression was upregulated in livers derived from ob/ob, db/db and diet-induced obesity (DIO) mice. Liver PLZF-overexpressing C57BL/6J mice showed fatty liver phenotype, liver inflammation, impaired glucose tolerance and insulin sensitivity. On the other hand, hepatic PLZF knockdown in db/db and DIO mice alleviated hepatic steatosis. Of note, we found that PLZF activates SREBP-1c gene transcription through binding directly to the promoter fragment of this gene, which would induce a repressor-to-activator conversion depending on its interaction with SIRT1 in the role played by PLZF in the transcription process through deacetylation. Thus, PLZF is identified as an essential regulator of hepatic lipid and glucose metabolism, where the modulation of its liver expression could open up a therapeutic path for treating NAFLD.